2012
DOI: 10.1016/j.physletb.2012.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a new boson at a mass of 125 GeV with the CMS experiment at the LHC

Abstract: Results are presented from searches for the standard model Higgs boson in proton-proton collisions at root s = 7 and 8 TeV in the Compact Muon Solenoid experiment at the LHC, using data samples corresponding to integrated luminosities of up to 5.1 fb(-1) at 7 TeV and 5.3 fb(-1) at 8 TeV. The search is performed in five decay modes: gamma gamma, ZZ, W+W-, tau(+)tau(-), and b (b) over bar. An excess of events is observed above the expected background, with a local significance of 5.0 standard deviations, at a ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

159
8,639
6
50

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 8,555 publications
(9,020 citation statements)
references
References 103 publications
159
8,639
6
50
Order By: Relevance
“…With the recent discovery of a Higgs-like particle with a mass of about 125 GeV by both the ATLAS [1] and CMS [2] collaborations, the focus has now turned to deciphering the properties of this particle and determining whether it is the Standard Model (SM) Higgs particle, or part of an extended Higgs sector. Analyses performed by ATLAS and CMS collaborations have shown that the couplings of the newly discovered particle are consistent with a SM-like Higgs boson, within the accuracy of their measurements.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent discovery of a Higgs-like particle with a mass of about 125 GeV by both the ATLAS [1] and CMS [2] collaborations, the focus has now turned to deciphering the properties of this particle and determining whether it is the Standard Model (SM) Higgs particle, or part of an extended Higgs sector. Analyses performed by ATLAS and CMS collaborations have shown that the couplings of the newly discovered particle are consistent with a SM-like Higgs boson, within the accuracy of their measurements.…”
Section: Introductionmentioning
confidence: 99%
“…For renormalization scheme, the on-shell scheme is used, in which input parameters to determine electroweak couplings are W -boson and Z -boson masses, and the fine-structure constant. The Weinberg mixing angle is obtained using the on-shell condition, sin 2 …”
Section: Resultsmentioning
confidence: 99%
“…The discovery of the Higgs boson [1,2] in 2012 showed the standard theory of particle physics to be well established. Even though the standard theory can describe the microscopic nature at a subatomic level very precisely [3], it cannot be the most fundamental theory of nature because, for instance, it includes many parameters (e.g., particle masses and couplings, number of generations) that are not determined within the theory.…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of the Higgs boson [1,2], the investigation of that particle has become one of the most important problems for the particle physics, especially the verification of the mass generation mechanism. In the Standard Model (SM), the Yukawa coupling of matter fermions with the Higgs boson is proportional to the fermion mass.…”
Section: Introductionmentioning
confidence: 99%